Body dysmorphic disorder : a treatment manual - Veale, David; Neziroglu, Fugen A., 1951- (Chichester, West Sussex, UK ; Malden, MA : Wiley-Blackwell, 2010)
This book is a unique treatment manual which looks at the assessment of BDD, offering an treatment model in the form of CBT and pharmacotherapy: Summarises the current knowledge and theoretical perspectives about BDD; Covers the practical aspects of assessment, engagement, and therapy; Uses a number of practical resources, including client handouts.
The diagnosis of body dysmorphic disorder -- History of body dysmorphic disorder -- Epidemiology and presentation of BDD -- Descriptive psychopathology of BDD -- Psychogenic excoriation -- Psychological aspects of cosmetic procedures -- Risk factors in for the development of BDD -- Neurobiological aspects of BDD -- Learning theory models of BDD -- Cognitive behavioural models of BDD -- Evidence for cognitive behaviour therapy in BDD -- Evidence for pharmacotherapy in BDD -- Assessment -- Engagement and formulation -- Advice on cosmetic procedures -- Imagery rescripting -- Modifying attentional biases -- Modifying cognitive processes -- Safety seeking, compulsive and avoidance behaviours -- Modifying appraisals -- Habit reversal for psychogenic excoriation -- Behavioural activation for depression -- Pharmacotherapy.
Includes bibliographical references (pages 441-471) and index.
Print version record.
Keywords: Body dysmorphic disorder -- Treatment -- Handbooks, manuals, etc; Somatoform Disorders -- therapy; Body image; Obsessive-Compulsive Disorder -- therapy; Self concept; Body dysmorphic disorder; Handbooks, manuals, etc; Treatment; Medicine; PSYCHOLOGY -- Neuropsychology; Electronic books